Estudo de casos na promoção da argumentação sobre questões sócio-científicas no ensino superior de química - Sá, Luciana Passos (2010)
This study was guided mainly in the application of the case study method of instruction. We analyzed the students‟ argumentation on socio-scientific issues in an undergraduate chemistry course in Brazil. Firstly, we investigated the place of argumentation in undergraduate chemistry teaching, created fourteen cases, and characterized them as structured, ill-structured, and multiple problems based on the Ideal Problem- Solving Model. Next, groups of students presented their solutions to the cases orally and participated in debates on the subject. The cases were applied in two different contexts: first, the argumentation occurred spontaneously; second, the students were instructed about the characteristics of a good argument. Considering the different contexts, we investigated if the students that were taught to argue, based on Toulmin Model, would developed this skill better. Furthermore, we developed an argumentation model of analysis appropriated to assess other relevant aspects related to the arguments elaborated by the students in discussions of socio-scientific issues. This model, called Argumentation Model of Analysis Applicable to Processes of Resolution of Socio-Scientific Issues, was applied aiming at understanding the nature of the arguments, argumentative strategies, and the sources of evidence usually employed by the students to solve the cases. From this perspective, we evaluated the quality of argumentation in discussions on socio-scientific issues and observed to what extent the method of case study favored the development of arguments. The perceptions of the students on the teaching proposals were also investigated through questionnaires. The conclusions of the study indicated that the discourse observed in undergraduate chemistry teaching was teacher dominated and tended not to foster the reflective discussion of scientific and/or socio-scientific issues. Structural analysis of the arguments indicated that to teach students about the characteristics of a good argument favored the development of more elaborated arguments. The Argumentation Model of Analysis Applicable to Processes of Resolution of Socio-Scientific Issues showed that the type of cases influences the types of learning strategies, the nature of the criteria considered in the analysis of the problem, and the sources of evidence employed to their solution. Moreover, we found that certain strategies are strongly encouraged in situations of oral presentations, whereas others are encouraged in situations of debates. The xv proposed model was adequate to our purposes, and it may also be useful in other situations involving problem solving on socio-scientific issues. The teaching strategies were well received by the students. We believe that the results can provide guidance for directing future research in Science Education related to the development of teaching strategies favorable to the practice of argumentation.